Secondary Amenorrhea After Hodgkin’s Lymphoma Is Influenced by Age at Treatment, Stage of Disease, Chemotherapy Regimen, and the Use of Oral Contraceptives During Therapy: A Report From the German Hodgkin’s Lymphoma Study Group - Behringer, Karolin; Breuer, Kai; Reineke, Thorsten; May, Michael; Nogova, Lucia; Klimm, Beate; Schmitz, Tatiana; Wildt, Ludwig; Diehl, Volker; Engert, Andreas (Journal of clinical oncology, 2005)
Long-term survivors of successfully treated Hodgkin's lymphoma (HL) are at risk for late complications. Among these, infertility for female patients is of major importance. The subject of this analysis is to evaluate the menstrual status after HL therapy. From 1994 to 1998, the German Hodgkin's Lymphoma Study Group conducted clinical trials for early-, intermediate-, and advanced-stage HL (trials HD7 to HD9) involving a total of 3,186 patients. A survey was carried out to evaluate the menstrual status after therapy. The following factors were assessed concerning their influence on amenorrhea: age, treatment, stage, and the use of oral contraceptives during chemotherapy. A total of 405 women aged younger than 40 years answered the study questions. After a median follow-up of 3.2 years, 51.4% of the women receiving eight cycles of dose-escalated bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone (BEACOPP) had continuous amenorrhea. Amenorrhea was significantly more frequent after dose-escalated BEACOPP compared with doxorubicin, bleomycin, vinblastine, and dacarbazine; cyclophosphamide, vincristine, procarbazine, prednisone, doxorubicin, bleomycin, vinblastine, and dacarbazine; or standard BEACOPP (P = .0066). Amenorrhea after therapy was most pronounced in women with advanced-stage HL (P < .0001), in women older than 30 years at treatment (P = .0065), and in women who did not take oral contraceptives during chemotherapy (P = .0002). Most women who are treated for advanced-stage HL experience amenorrhea after therapy. Amenorrhea is significantly more frequent in women with advanced-stage HL receiving eight cycles of dose-escalated BEACOPP and in women older than 30 years at first treatment. Furthermore, the data show a statistical association between the use of oral contraceptives and return of menstrual cycle, which is subject to further investigation.